(3GdeLJHi ef GdeLJHis - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe Hf GdLhRi gPG cJGH ELJHjJ ajg eeG ELJfHJ ef Ydhe eNJdaI aUd GdNWGH ai GdbQBf s
(3BNQgG (B:s
(3cGf GdNdjaI YfO QCS GdSJjf hNeS eGjI GdeSJfLO HGddg hGdabjg CHh jYdi eMeO Hf eMeO Hf GdaQGA hGdRGgO GdMSf Hf eSde GdaGQSi BNQ GdcJGH hGdMeO ddg hMOg s
(3cJGH ai CfhGY TJi ef GdYdhes
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1592s
Keywords: (3GdJUha hGdBOGH GdTQYjIs